Legal aid and pro bono service - Sardar Baig, Farheen Baig; Ali Mohamed, Ashgar Ali; Mirza Farhad Baig, Farhana (CLJ Malaysia Sdn. Bhd., 2025)
There must be equality between the parties and both parties must have the right to legal representation. In fact, the right to legal representation in a criminal justice system is recognised in the “United Nations Principles and Guidelines on Access to Legal Aid in Criminal Justice Systems” adopted on 25 April 2012 by the United Nations Economic and Social Council. Furthermore, it is also guaranteed as both a constitutional and statutory right in Malaysia.2 Article 5(3) of the Federal Constitution provides, inter alia, that “where a person is arrested he shall be informed as soon as may be of the grounds of his arrest and shall be allowed toconsult and be defended by a legal practitioner of his choice”. If such rights are curtailed, the “Constitution would cease to have effect and the protection accorded to the citizens in the Constitution would become illusory”.3 Likewise, s. 28 of the Criminal Procedure Code and s. 104 of the Syariah Criminal Procedure (Federal Territories) Act 1997 provide that every person accused before any court may, of right, be defended by a lawyer (or Peguam Syarie in the Syariah Court).